Agriculture-associated diseases: Adapting agriculture to improve human health - McDermott, John J.; Grace, Delia (International Livestock Research Institute, 2011)
Agriculture and health are intimately linked. Many diseases have agricultural roots—food-borne diseases, water-associated diseases, many zoonoses, most emerging infectious diseases, and occupational diseases associated with agrifood chains. These diseases create an especially heavy burden for poor countries, with far-reaching impacts. This brief views agriculture-associated disease as the dimension of public health shaped by the interaction between humans, animals and agroecoystems. This conceptual approach presents new opportunities for shaping agriculture to improve health outcomes, in both the short and long terms.